Studi Komparatif: Harga Saham LQ45 Sebelum Dan Selama Masa Pandemi Covid-19 - Suwadji, Sukma Annisa; Lestari, Rahayu; Abdunnafi, Fauziah Istiqomah (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Research Aim: This study re-evaluates the impact of the COVID-19 pandemic on LQ45 stock prices Methods: Data from 2018-2021 are analyzed, with 2018-2019 representing pre-pandemic prices and 2020-2021 representing pandemic prices. Comparative analysis is conducted using average t-tests, with normality tests guiding the choice between paired sample t-tests and Wilcoxon signed-rank tests Findings: Data exhibited a non-normal distribution, revealing a significant 27% average decrease in LQ45 stock prices during the pandemic. This underscores the pandemic's substantial impact on stock prices, particularly within the LQ45 index Theoretical Contribution/Originality: This study corroborates earlier findings and provides empirical evidence of the significant difference in LQ45 stock prices before and during COVID-19, resolving previous inconsistencies Practitioner/Policy Implication: The COVID-19 pandemic negatively affects stock prices, signaling adversity to investors and prompting market reactions, leading to decreased stock values. The LQ45 index experienced a decline in share prices from 2020 to 2021, highlighting the pandemic's enduring impact on market dynamics Research Limitation: This study focuses solely on the COVID-19 impact on LQ45 stock prices using year-end closing prices. Future research could explore this influence further using monthly or quarterly stock data